Exports under the Flicker of the Northern Lights - Helga Kristjánsdóttir (Kiel Institute for the World Economy (IfW), 2008)
Picture a small open economy in the North Atlantic Ocean, highly dependent on trade with the EU and NAFTA. How important are these trading blocs to the country's exports? How important is the country's location and size, and how do these affect the export sectors? A unique version of the gravity model is applied here using an inverse hyperbolic sine function. Typically, the export volume is significantly impacted by the economic size of the exporting country, but in this case it is not. This suggests that the exports from small remote economies are driven by different factors than exports from large conomies.
Keywords: C23; F14; F15; F1; 330; Exports; gravity model; free trade agreements; panel data; Export; Kleines-offenes-Land; Gravitationsmodell; Island; EU-Staaten; NAFTA-Staaten